Microalgae Ankistrodesmus gracilis as feed ingredient for ornamental fish Xiphophorus maculatus - Sipauba-Tavares, Lucia H. [UNESP]; Fernandes, Joao B. K. [UNESP]; Melo-Santos, Gustavo L. [UNESP]; Scardoeli-Truzzi, Bruno [UNESP] (Springer, 2019)
A trial evaluated the effectiveness of macrophytes, Azolla caroliniana (AAC) and Lemna minor (ALM) as a culture media for microalgae Ankistrodesmus gracilis, and their possible use as feed ingredient for ornamental fish. Water quality in all aquariums was adequate for the growth of Xiphophorus maculatus, whilst pH acidity in inert diet (ID) treatment and high content of P in AAC diet treatment did not interfere in fish development. Growth performance parameters were higher (P<0.05) in ALM diet treatment, except condition factor and feed conversion ratio, with similar rates (P>0.05) in all diet treatments. Survival was above 75% and total length was similar (P>0.05) for ID and AAC diet treatments. Lipid levels ranged between 7 and 11%, and was enough to maintain high survival rates (>80%) and weight gain above 0.42g to mixed diet (AAC and ALM) and 0.27g to inert diet. Ankistrodesmus gracilis and macrophytes as a culture media are useful as functional ingredients, because biomass may be incorporated with the food supplement for X. maculatus to enhance nutrition quality and to maintain high growth performance. Although A. caroliniana and L. minor may be used with culture media, L. minor provided the best results to microalgae growth biomass and ornamental fish.